Evaluation of sweep modes for switch response on ferroelectric negative-capacitance FETs. (19th June 2019) - Chen, Kuan-Ting; Chou, Yu-Chen; Siang, Gao-Yu; Chen, Hong-Yu; Lo, Chieh; Liao, Chun-Yu; Chang, Shu-Tong; Lee, Min-Hung
Abstract: The sweep modes of gate voltages correlate with the characteristics of ferroelectric negative-capacitance field-effect transistors. Both DC steps and AC pulse sweeps are applied to evaluate the switch response and establish a related model. The subthreshold swing (SS) is unchanged in a DC sweep speed range of 640 μ s step −1 to 267 ms step −1 . An improved SS is obtained using an AC pulse sweep due to its more stimulated charge for polarization by a multiple-pulse trigger, and the related model is presented with the classical spring–mass system concept.